Can the pattern of juvenile recruitment and population structure of the speckled swimming crab Arenaeus cribrarius (Decapoda: Brachyura) be determined by geographical variations? - de Andrade, Luciana Segura [UNESP]; Frameschi, Israel Fernandes [UNESP]; Castilho, Antônio Leão [UNESP]; da Costa, Rogério Caetano [UNESP]; Fransozo, Adilson [UNESP] (Wiley, 2015)
This study evaluated the effect of environmental stimuli and selective pressures in different geographical areas along a latitudinal gradient, on the juvenile recruitment, population structure, and sex ratio of the speckled swimming crab Arenaeus cribrarius. Samples were collected monthly during 1 year in three locations along the Brazilian coast: Macaé, state of Rio de Janeiro (MAC, 22°47′ S, 41°45′ W); Ubatuba, São Paulo (UBA, 23°27′ S, 44°58′ W); and São Francisco do Sul, Santa Catarina (SFS, 26°08′ S, 48°34′ W). The specimens of A. cribrarius were identified, counted, sexed, and measured for maximum carapace width (CW). The largest juvenile found was in UBA (47.7 ± 1.36 mm); and the largest adult females and males in MAC (74.26 ± 0.93 and 77.04 ± 0.79 mm, respectively). Recruitment in MAC was continuous, whereas in UBA and SFS, recruitment showed seasonal characteristics. The sex ratio was skewed toward females only in UBA; in MAC and SFS, males and females were present in equal proportions. These results indicate that geographical variations can cause differences in the recruitment and population structure of A. cribrarius. These regional differences call attention to the necessity for improved management plans and control of shrimp fishing, which can affect population patterns such as juvenile recruitment, population structure and life history of the target species and species that are caught in bycatch from shrimping, such as the swimming crab A. cribrarius.
Keywords: Arenaeus cribrarius; Crustacea; Latitudinal trends; Population patterns; Portunid; Size rate